Paying for the view? How nursing home prices affect quality of care - Dörte Heger; Annika Herr; Anne Mensen (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
Increasing long-term care demand raises the need of high quality care in nursing homes. This study analyses whether higher prices have a causal effect on quality of care in Swiss nursing homes and assesses the extent of cross-subsidization between different price components. We use administrative data collected by the Swiss Federal Office for Statistics from 2012 to 2016 on all nursing homes in the twelve Swiss cantons with canton-wide fixed reimbursement rates for nursing care. We apply multivariate linear regressions and two-stage least square estimation techniques to estimate the effect of nursing care prices and prices for accommodation and services on care quality, measured by registered staffing levels. Our estimates show a positive impact of all price components on care quality. Although nursing homes are prohibited to use revenues from accommodation and services to cover nursing care, a 10% increase in that price component increases certified staffing levels by 0.7 to 1.7 nurses or four to ten percent (full-time-equivalent) for an average sized nursing home (50 beds). Thus, limiting care prices implicitly sets a limit for care quality and induces care providers to pass on costs to the residents. – – Die steigende Nachfrage nach Langzeitpflege erhöht den Bedarf an qualitativ hochwertiger Pflege in Pflegeheimen. In dieser Studie wird untersucht, ob höhere Preise einen Einfluss auf die Versorgungsqualität in Schweizer Pflegeheimen haben, und das Ausmaß der Quersubventionierung zwischen verschiedenen Preiskomponenten bewertet. Wir verwenden administrative Daten aller Pflegeheime der zwölf Schweizer Kantone mit kantonalen Festbeträgen für die Altenpflege, die das Bundesamt für Statistik für die Jahre 2012 bis 2016 erhoben hat. Wir wenden multivariate lineare Regressionen und 2SLS an, um die Auswirkungen von Pflegepreisen und Preisen für Unterkunft und Dienstleistungen auf die Pflegequalität, gemessen am Personalbestand an Pflegefachkräften, zu schätzen. Unsere Ergebnisse zeigen einen positiven Einfluss aller Preiskomponenten auf die Pflegequalität. Zwar ist es Pflegeheimen nicht gestattet Einnahmen aus Unterkünften und Dienstleistungen für die Pflege zu verwenden, doch erhöht eine um 10% erhöhte Preiskomponente die Zahl der Pflegefachkräfte um 0,7 bis 1,7 Pflegefachkräfte (Vollzeitäquivalent) bzw. um vier bis zehn Prozent bezogen auf ein durchschnittlich großes Pflegeheim (50 Betten). Die Begrenzung der Pflegepreise setzt somit implizit eine Grenze für die Pflegequalität und bewirkt, dass die Leistungserbringer die Kosten für Pflege an die Bewohner weitergeben.
Keywords: I11; I18; J18; 330; long-term care; nursing home; prices; care quality; staffing levels